A prototype proposal for mobile pervasive augmented reality systems: improving the quality of experience in outdoor sports environments - Pascoal, R.; Galego, N. (Sustainable Development, Landscape Planning and Territorial Governance - Book of abstracts, 2021)
This work describes the deployment of the mobile pervasive augmented reality system for outdoor sports environments. This prototype relies on heuristics that combine user preference indicators of technology adoption, sensing criteria, and volume of information criteria to provide real-time adaptation of the display without information overload, resulting in a better Quality of Experience for the end-user. Experiments show the performance evaluation for technology adoption in outdoor sporting environments, with real-time adaptation based on a developed algorithm. The findings show what and how much information must show to avoid information overload.